The anthology of rap - Bradley, Adam; DuBois, Andrew (Andrew Lee); Gates, Henry Louis, Jr; Chuck D, 1960-; Common (Musician) (Yale University Press, 2010)
Rap has emerged as one of the most influential cultural forces of our time. In this work, the editors demonstrate that rap is also a wide reaching and vital poetic tradition born of beats and rhymes. This pioneering anthology brings together more than three hundred lyrics written over thirty years, from the "old school" to the "golden age" to the present day. Rather than aim for encyclopedic coverage, the editors render through examples the richness and diversity of rap's poetic tradition. They feature classic lyrics that helped define the genre as well as lesser known gems. Both a fan's guide and a resource for the uninitiated, this book showcases the inventiveness and vitality of rap's lyrical art, also providing an overview of rap poetics and the forces that shaped each period in rap's historical development.--From publisher description